Wordsworth’s Creation of Active Taste - Jones, Chris; Lee, Li-Po (Romanticism and Victorianism on the Net, 2009)
AbstractBuilding on Bakhtinian approaches to Wordsworth’s early poems, we extend their findings to The Prelude, using analytical tools from narratology and film criticism to trace the interplay of different views and voices. By dramatising his narrator and his problems in suturing together past and present and the viewpoints of the young “hero” and the older narrator, Wordsworth the poet is continuing his project of educating an active taste. The narrator demonstrates the processes of the imagination but in ways that reveal its artifice for others to use. The gaps and uncertainties which critics often see as suppressions are invitations for the reader to exercise a revisionary activity of his own in recognising the possibility of different stories from that which the narrator tries to tell. We analyse visual images for their dissonant suggestions and the manipulations of viewpoint that problematize any secure unity of purpose other than that of suturing the reader into the creative community that Wordsworth hails at the conclusion.